2008
DOI: 10.1248/cpb.56.260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a .BETA.-Tetrapeptide Analog as a Mother Compound for the Development of Matrix Metalloproteinase-2-Imaging Agents

Abstract: Matrix metalloproteinases (MMPs) comprise a family of enzymes that degrade the basement membrane and extracellular matrix, thus contributing to tissue remodeling and cell migration. 1,2) Numerous studies have demonstrated the various roles of MMPs in pathological processes associated with cancer and atherosclerosis, making MMPs potential targets for diagnosis using noninvasive imaging.3,4) Among MMPs, MMP-2, which degrades a major component of the basement membrane, has been studied extensively and shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.03 (s, 1H, NH), 7.65 (d, J = 7.5 Hz, 1H, CHAr), 7.43–7.28 (m, 6H), 7.21 (t, J = 7.5 Hz, 1H, CHAr), 7.15–7.07 (m, 1H, CHAr), 7.03 (s, 1H, CHAr), 5.10 (s, 2H, CH 2 Ph), 5.04 (br s, 1H, NH), 4.16–3.95 (m, 1H, CH), 3.68 (ddd, J = 15.4, 9.7, 4.2 Hz, 2H, CCH 2 CH), 3.03 (d, J = 6.8 Hz, 2H, CH 2 OH). Data in accordance with the literature. , …”
Section: Methodssupporting
confidence: 78%
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.03 (s, 1H, NH), 7.65 (d, J = 7.5 Hz, 1H, CHAr), 7.43–7.28 (m, 6H), 7.21 (t, J = 7.5 Hz, 1H, CHAr), 7.15–7.07 (m, 1H, CHAr), 7.03 (s, 1H, CHAr), 5.10 (s, 2H, CH 2 Ph), 5.04 (br s, 1H, NH), 4.16–3.95 (m, 1H, CH), 3.68 (ddd, J = 15.4, 9.7, 4.2 Hz, 2H, CCH 2 CH), 3.03 (d, J = 6.8 Hz, 2H, CH 2 OH). Data in accordance with the literature. , …”
Section: Methodssupporting
confidence: 78%
“…Mukai et al found that H-β 3 -Phe-β-Ala-β 3 -Trp-β 3 -His-OH inhibited MMP-2 with an IC 50 value of 225 µM, in comparison to CTT IC 50 of 212 µM (as determined herein) [31]. Linear α-tetrapeptide had no significant contribution towards MMP inhibition, with an IC 50 value of >1 mM [31]. While H-β 3 -Phe-β-Ala-β 3 -Trp-β 3 -His-OH has a similar affinity for MMP-2 as CTT, the new class of β-tetrapeptide is smaller in size and generally more stable, thereby enhancing its accumulation in target tissues.…”
Section: Peptides That Target Gelatinase Members Of the Mmp Familymentioning
confidence: 60%
“…The linear β-tetra peptide H-β 3 -Phe-β-Ala-β 3 -Trp-β 3 -His-OH was designed to mimic CTT. Mukai et al found that H-β 3 -Phe-β-Ala-β 3 -Trp-β 3 -His-OH inhibited MMP-2 with an IC 50 value of 225 µM, in comparison to CTT IC 50 of 212 µM (as determined herein) [31]. Linear α-tetrapeptide had no significant contribution towards MMP inhibition, with an IC 50 value of >1 mM [31].…”
Section: Peptides That Target Gelatinase Members Of the Mmp Familymentioning
confidence: 68%
“…Allylbenzene, 4-phenylbut-1-ene and Meldrum's acid were from Aldrich. (2,4,acetic acid was from Matrix Scientific. The solvents were of the highest analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…Racemic b-lactams (±)-3 and (±)-4 were prepared by the addition of chlorosulfonyl isocyanate to allylbenzene (1) or 4-phenylbut-1ene (2), respectively, according to known literature methods. 19b,24 (±)-3 and (±)-4 (6.0 mmol) were then refluxed with 22% HCl/EtOH (15 mL) for 8 h, after which the solvent was evaporated off, resulting in the corresponding b-amino ester hydrochlorides (±)-5•HCl and (±)-6•HCl, which were immediately treated with aqueous K 2 CO 3 to afford (±)-5 and (±)-6, as oils.…”
Section: Syntheses Of B-amino Esters (±)-5 and (±)-6mentioning
confidence: 99%